2018
DOI: 10.3390/s18010288
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Infrared Thermography for Fiber Orientation Assessment on Randomly-Oriented Strands Parts

Abstract: The use of fiber reinforced materials such as randomly-oriented strands has grown in recent years, especially for manufacturing of aerospace composite structures. This growth is mainly due to their advantageous properties: they are lighter and more resistant to corrosion when compared to metals and are more easily shaped than continuous fiber composites. The resistance and stiffness of these materials are directly related to their fiber orientation. Thus, efficient approaches to assess their fiber orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Roemer et al [ 93 ] compared LST with UST (see Section 3 ) to detect fatigue cracks on an aluminium sample ( Figure 10 ). Khodayar et al [ 94 ] used robotized Line Scan Thermography to inspect large composite materials, whilst Zhang et al [ 95 ] used pulsed micro-laser line thermography to detect submillimeter porosity in CFRP composites. Fernandes et al [ 96 ] employed a flying laser spot to heat a line region on a CFRP sample and assess the fiber orientation over that region.…”
Section: Optically Stimulated Thermographymentioning
confidence: 99%
“…Roemer et al [ 93 ] compared LST with UST (see Section 3 ) to detect fatigue cracks on an aluminium sample ( Figure 10 ). Khodayar et al [ 94 ] used robotized Line Scan Thermography to inspect large composite materials, whilst Zhang et al [ 95 ] used pulsed micro-laser line thermography to detect submillimeter porosity in CFRP composites. Fernandes et al [ 96 ] employed a flying laser spot to heat a line region on a CFRP sample and assess the fiber orientation over that region.…”
Section: Optically Stimulated Thermographymentioning
confidence: 99%
“…Sub-surface artificial defects in composite sandwich panels (commonly used materials in aircraft applications) could be identified using Laser-Line Thermography (LLT) [43][44]. Feasibility of Laser-Spot Thermography (LST), Laser-Line Thermography (LLT) and Ultrasonic Stimulated Thermography (UST) for inspections of composite materials, employed in aircraft industry, such as metallic turbine blades, aluminium samples, CFRP composites etc., to name few, was also assessed in several investigations [45][46][47][48][49].…”
Section: Applications Of Thermography For Aircraft Compositesmentioning
confidence: 99%
“…It was concluded that the detection accuracy of the proposed NN for the simulated data and the experimental data was 97% and 90% respectively. The artificial neural network algorithm was also combined with what so called Pulsed Thermal Ellipsometry (PTE) to investigate the fiber orientation on laminates reinforced with randomly-oriented strands [87]. Different CFRP samples were experimented using two thermography heating approaches.…”
Section: Applications Of Thermography For Aircraft Compositesmentioning
confidence: 99%
“…These data must be processed to extract knowledge about the inner structures of composite components. With this regard, machine learning can play a key role in defect and damage assessment [ 16 , 17 , 18 , 19 , 20 ]. Deep learning is a machine learning approach that is based on neural networks.…”
Section: Introductionmentioning
confidence: 99%